Guidance document for prevention of Clostridium difficile infection in acute healthcare settings. (October 2018) - Tschudin-Sutter, S.; Kuijper, E.J.; Durovic, A.; Vehreschild, M.J.G.T.; Barbut, F.; Eckert, C.; Fitzpatrick, F.; Hell, M.; Norèn, T.; O'Driscoll, J.; Coia, J.; Gastmeier, P.; et al.
Abstract: Scope: Clostridium difficile infection (CDI) is the most important infective cause of healthcare-associated diarrhoea in high income countries and one of the most important healthcare-associated pathogens in both Europe and the United States. It is associated with high morbidity and mortality resulting in both societal and financial burden. A significant proportion of this burden is potentially preventable by a combination of targeted infection prevention and control measures and antimicrobial stewardship. The aim of this guidance document is to provide an update on recommendations for prevention of CDI in acute care settings to provide guidance to those responsible for institutional infection prevention and control programmes. Methods: An expert group was set up by the European society of clinical microbiology and infectious diseases (ESCMID) Study Group for C. difficile (ESGCD), which performed a systematic review of the literature on prevention of CDI in adults hospitalized in acute care settings and derived respective recommendations according to the GRADE approach. Recommendations are stratified for both outbreak and endemic settings. Questions addressed by the guideline and recommendations: This guidance document provides thirty-six statements on strategies to prevent CDI in acute care settings, including 18 strong recommendations. No recommendation was provided for three questions.